Policy reforms and the amount of checks & balances - Hans Gersbach; Oriol Tejada; Julia Wagner (ETH Zurich, CER-ETH - Center of Economic Research, 2022)
We examine how democracies choose their amount of checks and balances (C&B). For this purpose, we consider a simple model of political competition with costly policy reforms. The cost of a marginal reform is determined endogenously at the constitutional phase-i.e. before policies are chosen-through the choice of (the amount of) C&B. We characterize the set of stable C&B for different constitutional rules which vary depending on (i) who has the power to propose changes to C&B and (ii) on the qualified majority used for approving such changes. Our main results show that stable C&B always exist, are never zero, lead to gridlock, and are higher if the proposal-maker is the party in government. We also find that higher majority requirements for constitutional changes and more polarized societies are conducive to larger sets of stable C&B.
Keywords: C72; D72; D78; H4; 330; elections; democracy; political polarization; reform costs; constitutions; checks and balances